2015
DOI: 10.2147/copd.s85432
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors, and health-related quality of life of osteoporosis in patients with COPD at a community hospital in Taiwan

Abstract: BackgroundData regarding osteoporosis in COPD patients in Taiwan remain limited. The primary end point of this study was to evaluate the prevalence and risk factors of osteoporosis in COPD patients in Taiwan. The secondary end point was to examine the association between osteoporosis and health-related quality of life (HRQL) in COPD patients.Materials and methodsThis prospective cross-sectional study enrolled 125 COPD patients (mean age 73.6 years, forced expiratory volume in 1 second [FEV1] 1.19±0.43 L) who h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 42 publications
2
20
2
Order By: Relevance
“…[6] These are the stage of COPD as measured by FEV1, hypoxia, dyspnea score, and emphysema. [48913142628] Similar to our findings studies are nearly unanimous on the presence of an association between FEV1 and the severity of osteoporosis. [272628] Although the stage of COPD was shown to be an independent risk factor for osteoporosis, it is likely that the association is further enhanced by other factors prevalent in advanced COPD such as cachexia, skeletal muscle weakness, and reduced mobility.…”
Section: Discussionsupporting
confidence: 90%
“…[6] These are the stage of COPD as measured by FEV1, hypoxia, dyspnea score, and emphysema. [48913142628] Similar to our findings studies are nearly unanimous on the presence of an association between FEV1 and the severity of osteoporosis. [272628] Although the stage of COPD was shown to be an independent risk factor for osteoporosis, it is likely that the association is further enhanced by other factors prevalent in advanced COPD such as cachexia, skeletal muscle weakness, and reduced mobility.…”
Section: Discussionsupporting
confidence: 90%
“…Manuscript to be reviewed osteoforosis in our study was lower than the 40% reforted in a recent study also conducted in Chiayi, Taiwan (Lin et al, 2015). This may be exflained by differences in subject enrollment and osteoforosis definition.…”
Section: Discussioncontrasting
confidence: 68%
“…Furthermore, Sin and Man found that the negative association between CRP, and FEV1 and FVC, in COPD fatients was much stronger in men than in women (Sin & Man, 2003). These findings suggest that fersistent systemic inflammation in COPD links worse lung condition with extra-fulmonary comorbidities such as osteoforosis or general cachexia and exflains why some studies revealed that foor fulmonary function farameters such as FEV1 were associated with osteoforosis develofment (Lin et al, 2015;Watanabe et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, cumulative results of these studies are inconclusive, and the definite fathogenic mechanism remains unclear. To our knowledge, data regarding risk factors in Taiwan are limited, with no current research regarding the association between inflammation markers or systemic inflammation and osteoforosis develofment Lee et al, 2016;Lin et al, 2015;Liu et al, 2015). Therefore, this study frimarily aimed to investigate risk It enrolled male COPD fatients aged ≥45 years from a chest outfatient clinic in a regional teaching hosfital in the west Chiayi County, Taiwan.…”
Section: Introductionmentioning
confidence: 99%